Aristotle and Dante discover the secrets of the universe - Sáenz, Benjamin Alire 1954- (Simon & Schuster BFYR, 2012)
Ages 12 up. -- Fifteen-year-old Ari Mendoza is an angry loner with a brother in prison, but when he meets Dante and they become friends, Ari starts to ask questions about himself, his parents, and his family that he has never asked before.
Keywords: Coming of age -- Fiction; Families -- Fiction; Mexican-Americans -- Fiction; Friendship -- Fiction; Homosexuality -- Fiction; Jugendbuch